Ecotourism Strategy in Facing the New-Normal Era (Case Study: Ecowisata Gunung Anyar) - Wiwik Dwi Susanti; Muchlisiniyati Safeyah; Fairuz Mutia (Future Science, 2020)
The COVID-19 pandemic has changed all aspects of life including people's habits of traveling and traveling. People limit themselves to mobilization to avoid spreading the virus. But that does not mean tourist attractions do not have the opportunity to rise again during the new normal era. According to the Director of the Indonesia Ecotourism Network, Ary Suhandi, in the new normal era, the trend of large numbers of tourism (mass tourism) is predicted to be replaced by the trend of quality tourism.